Perancangan Museum kesulthanan Aceh di Banda Aceh sebagai sarana edukasi dan rekreasi dengan penerapan tema cultural symbol - Tgk. Yumna Darayani; Irzaidi Irzaidi (Universitas Syiah Kuala, 2022)
This journal aims to interpret the history of Aceh through the kingdom of Aceh which was led by Sulthan-Sulthan who had a glorious leadership status in his time as a knowledge and also revealed the glory of Aceh. Telling Aceh is of course inseparable from the Acehnese Society, which has an extraordinary history and culture and is able to share with each other as a strenghth and make it a character of the people of Aceh. However, if we look at this generations, the Acehnese no longer have the knowledge or identity regarding the history of Acehnese (Kingdom of Aceh). Of course this needs a facility that is able to remind Acehnese people of their identity, which has brought Aceh to its glory. The Kesulthanan Museum is capable of carrying out its function to convey a reality that once existed as a means of education and also recreation (tourism). This process will not proceed on its own without any support that can ensure that Aceh has a very broad history and culture so that the application of this cultural symbol theme shows the expression of the Aceh Kesulthan Museum to Acehnese people that history is not only stored in books, poems or memories but it can make the image of Aceh again have an identity based on the Museum of Kesulthanan Acehnese.Abstrak